FACTOR ANALYSIS OF THE IMPLEMENTATION OF VISUAL INSPECTION OF ACETIC ACID (VIA) EXAMINATION IN WOMEN OF FERTILE AGE AT UJAN MAS HEALTH CENTER - Ikeliya, Aldesten; Harokan, Ali; Gustina, Erma (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Visual Inspection with Acetic Acid (VIA) is a low-cost and easy method for early detection of cervical cancer, but its implementation coverage remains low. This study aimed to analyze factors influencing VIA examination among women of reproductive age at Ujan Mas Health Center. A quantitative cross-sectional study was conducted involving 367 respondents selected through purposive sampling. Data were collected using validated questionnaires and analyzed through univariate, bivariate (chi-square), and multivariate (logistic regression) tests. Multivariate analysis revealed that age (p=0.018; OR=0.542), husband support (p=0.013; OR=1.933), and health cadre support (p=0.000; OR=10.393) were significantly associated with VIA examination. Cadre support emerged as the most dominant factor with a 53,9% probability contribution. Health cadre and husband support are crucial to enhancing VIA screening uptake. Knowledge, education, and access to information were not significantly associated in the final model. Strengthening the role of health cadres and involving husbands in health promotion interventions is recommended for improving early cervical cancer detection